TAINEUA LANGUAGE AND CULTURE - amphaithip, khampha (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The purpose of this research was to study the spoken language used in daily life and to collect cultural information about the Taineua people in Sing District, Luang Namtha Province. The data used in the study consisted of a vocabulary list of 150 words, tested with 15 native speakers aged 70 up. Data collection was conducted through interviews and interactive activities with local speakers. The linguistic data were analyzed using phonemic analysis, focusing on consonants, vowels, and tone markers. The results revealed that the Taineua spoken language includes 19 single consonant sounds and one diphthong consonant (/w/), but lacks the palatal nasal vowel sound (/ɲ/). Phonemic analysis identified 18 distinct phonemes and 3 compound phonemes. Tonal analysis showed the presence of 6 tone phonemes, with notable variations in tone splitting and combination patterns. In terms of cultural data, the study found that the Taineua maintain rich and unique cultural traditions, including distinctive clothing, water-splashing rituals, architectural styles, traditional foods, and beliefs in sacred entities and astrology. Some customs exhibit a blend of Buddhist and animistic beliefs, influenced by the surrounding societal and environmental context.